Renewable energy in Europe : markets, trends, and technologies (Earthscan, 2010)
"How can the European Union meet its binding 20% renewable energy target in final energy consumption by the year 2020? Which sources offer the best prospects for realizing this goal? These are the questions answered by this key book which analyses the current situation of renewable energy in Europe, examines the latest technological, financial and economic developments, and outlines ways in which the renewable energy market can be developed. The book is divided into sections examining the integration of renewable energy, electricity, heating and cooling as well as biofuels. All the main technologies are covered, with exploration of: benefits and applications; costs and prices; markets and installed capacity; policy instruments; key countries and success stories; and targets and long term potential. This will be essential reading for policy decision-makers at all levels and to all those involved in the development of the renewable energy industry."--Publisher's description.